2019
DOI: 10.1186/s12889-019-7231-1
|View full text |Cite
|
Sign up to set email alerts
|

Over-indebtedness and its association with sleep and sleep medication use

Abstract: Background Over-indebtedness is currently rising in high-income countries. Millions of citizens are confronted with the persistent situation when household income and assets are insufficient to cover payment obligations and living expenses. Previous research shows that over-indebtedness increases the risk of various adverse health effects. However, its association with sleep problems has not yet been examined. The objective of this study was to investigate the association between over-indebtedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 114 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…In the current study group, there was a higher percentage of professionals, and it is also possible that they would have been exposed to job challenges and increased digital screen time owing to ‘ work from home’ with no time restrictions on their jobs, more than any other persons, which might have resulted or contributed to increased insomnia. Even though longer screen time is reported to increase poor sleep quality by reducing sleep efficiency [ 53 ], this aspect was not included in the tool used for this study, and thus could not be assessed. Lower socioeconomic factors had been reported as a consistent predictor for both greater insomnia and excessive daytime sleepiness in a few studies [ 54 – 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study group, there was a higher percentage of professionals, and it is also possible that they would have been exposed to job challenges and increased digital screen time owing to ‘ work from home’ with no time restrictions on their jobs, more than any other persons, which might have resulted or contributed to increased insomnia. Even though longer screen time is reported to increase poor sleep quality by reducing sleep efficiency [ 53 ], this aspect was not included in the tool used for this study, and thus could not be assessed. Lower socioeconomic factors had been reported as a consistent predictor for both greater insomnia and excessive daytime sleepiness in a few studies [ 54 – 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confirming this pattern, a recent longitudinal study of Finnish adults found an association between over-indebtedness and an increased incidence of various chronic diseases ( Blomgren et al, 2016 ). More recently, Warth et al (2019) found a negative relationship between over-indebtedness and sleep quality. Notably, poor sleep plays a major role in a variety of health problems, from hypertension ( Gangwisch et al, 2006 ; Buxton and Marcelli, 2010 ; Meng et al, 2013 ) to diabetes ( Buxton and Marcelli, 2010 ; Morselli et al, 2012 ; Zizi et al, 2012 ; Grandner et al, 2014 ) and mortality ( Gallicchio and Kalesan, 2009 ; Grandner and Patel, 2009 ; Cappuccio et al, 2010 ; Grandner et al, 2010 ).…”
Section: Introductionmentioning
confidence: 96%
“…Financial debts contribute to psychological distress and suicidal behavior independent of gambling disorder (10,11). Over-indebtedness, which refers to an incapacity to fulfil payback requirements, is associated with depressive symptoms, suicidal ideation (12), and sleeping problems (13).…”
Section: Introductionmentioning
confidence: 99%